HLA-DR antigen linkage of anti-beta receptor antibodies in idiopathic dilated and ischaemic cardiomyopathy. Issue 5 (May 1992) - Limas, C J; Limas, C
Abstract : OBJECTIVE--Immunological mechanisms have been implicated in the pathogenesis of human dilated cardiomyopathy. The presence of autoantibodies against the beta 1 adrenoceptor in a substantial proportion of patients with dilated cardiomyopathy has been described and an association between the HLA-DR4 phenotype and anti-beta receptor antibodies has been identified. The objective of the present study was to examine whether the presence of such antibodies in ischaemic cardiomyopathy was limited to specific HLA-DR phenotypes. DESIGN--The HLA-DR dependence of anti-beta receptor antibodies detected by a ligand binding inhibition assay in patients with dilated cardiomyopathy (n = 68) was compared with that in patients with ischaemic cardiomyopathy (n = 73). RESULTS--38% of the patients with dilated cardiomyopathy and 22% of those with ischaemic cardiomyopathy had serum anti-beta receptor antibodies. In dilated cardiomyopathy, the presence of anti-beta receptor antibodies was linked to the HLA-DR4 phenotype (that is, 50% of patients with this phenotype were antibody positive) whereas, in those with ischaemic cardiomyopathy HLA-DR1 was over-represented (that is, 37% of the patients with the HLA-DR1 phenotype were antibody positive compared with 17% of the HLA-DR1 negative patients). In both disease entities, the HLA-DR3 phenotype was virtually absent in the anti-beta receptor antibody group. CONCLUSIONS--These results suggest that the presence of anti-beta receptor antibodies is under immune genetic control that may depend on the nature of the underlying disease process.